Values education in England and Wales... - Fearn, Mike; Francis, Leslie (Horyzonty Wychowania, 2017)
This paper demonstrates that practical theology can make animportant contribution to values education. Following an introductionto the values education framework within England andWales, attention is focused on a case study which illustrates thesexual values of young people. This illustration makes availablea seminal study published in the English language to a Polishaudience and shows the extent to which practical theology caninform values education.